2023
DOI: 10.1002/jsp2.1254
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 and RAGE differentially control advanced glycation endproduct‐induced collagen damage in murine intervertebral disc organ culture

Abstract: Background Back and neck pain are leading causes of global disability that are associated with intervertebral disc (IVD) degeneration. Causes of IVD degeneration are multifactorial, and diet, age, and diabetes have all been linked to IVD degeneration. Advanced glycation endproducts (AGEs) accumulate in the IVD as a result of aging, diet, and diabetes, and AGE accumulation in the IVD has been shown to induce oxidative stress and catabolic activity that result in collagen damage. An association between AGE accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…After ACG activation, Gal3 and RAGE can act as receptors of ACG to affect collagen, in which Gal3 has a protective effect on AGE attack, limiting collagen damage and biomechanical changes. RAGE is an essential receptor for collagen injury induced by AGEs ( 74 ). MRI image analysis showed that oral treatment with the AGE inhibitor PM could reduce NP dehydration after needle injury.…”
Section: Abnormal Glucose Metabolism and Iddmentioning
confidence: 99%
“…After ACG activation, Gal3 and RAGE can act as receptors of ACG to affect collagen, in which Gal3 has a protective effect on AGE attack, limiting collagen damage and biomechanical changes. RAGE is an essential receptor for collagen injury induced by AGEs ( 74 ). MRI image analysis showed that oral treatment with the AGE inhibitor PM could reduce NP dehydration after needle injury.…”
Section: Abnormal Glucose Metabolism and Iddmentioning
confidence: 99%
“…Furthermore, the expression of Galectin-3 is upregulated in nucleus pulposus cells and inhibition of Galectin-3 can alleviate spinal cord injury and intervertebral disc degeneration [ 22 ]. It has also been suggested that Galectin-3 may have a protective effect on cells and tissues involved in intervertebral disc degeneration, limiting collagen damage and changes in biomechanical properties [ 23 ]. However, there is no study on the expression and role of Galectin-3 in the cartilage endplate of the intervertebral disc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a Collagen Hybridizing Peptide (CHP) has been reported as being able to identify and quantify collagen damage in IVDs and other connective tissues at the molecular level. 9 , 14 , 21 , 22 , 23 , 24 , 25 Briefly, CHP binds selectively to the dissociated triple helix structure in the degraded collagens through a unique helix hybridization process, 12 , 21 mimicking the triple‐helical molecular structure of natural collagen, where it binds to the glycine (G)‐proline (P)‐hydroxyproline (O) amino acid repeat chains in the fibrillar triple helical domain. 12 Through hydrogen bonding, a stable homotrimeric triple helix is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that collagen denaturation was associated with the onset of mechanical damage. To date, only a few studies have examined the use of CHP to detect collagen damage in the AF, 9 , 14 , 23 , 25 of which only two use human AF. 9 , 23 However, the focus of those studies was on various murine models whereas human samples were not examined in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation